Ag2S nanoparticle-mediated multiple ablations reinvigorates the immune response for enhanced cancer photo-immunotherapy. (January 2021) - Han, Ruxia; Xiao, Yao; Yang, Qian; Pan, Meng; Hao, Ying; He, Xinlong; Peng, Jinrong; Qian, Zhiyong
Abstract: Photothermal therapy (PTT) has been widely used in cancer treatment in recent years. However, it is difficult to completely eliminate tumors by single PTT, and the effects of single dose of PTT frequency on the therapeutic outcome of PTT and the multiple PTT-induced immune response in cancer therapy also remain unclear. Here, water-soluble Ag2 S nanoparticles (NPs) with optimal particle size ( 15 nm) were synthesized and used as the PTT agents. The in vitro and in vivo results demonstrated that Ag2 S NPs had good photothermal conversion in response to the irradiation of an 808 nm laser, and the results indicated that the NPs have potential as contrast agents for photoacoustic imaging as well as good biocompatibility. The in vivo results further revealed that the frequency of the Ag2 S NP-mediated PTT affected the cancer therapeutic outcome. The increase of frequency efficiently reduced the primary tumor recurrence and alleviated metastasis. The present study suggested that the mechanism involves multiple PTT cycles inhibiting the proliferation of primary tumor cells and stimulating the systematic immune response in the mouse breast cancer model. Therefore, frequency optimization in photothermal ablation may provide a promising strategy to enhance the therapeutic outcome in cancer therapy.